Targeting Sphingosine-1-Phosphate Receptors in Cancer - Watters, Rebecca J. (2011)
Sphingosine 1-phosphate (S1P) is a bioactive lipid with diverse biological functions, including cell proliferation, differentiation, angiogenesis, chemotaxis, and migration. Many of the activities of S1P are mediated through five closely related G-protein-coupled receptors of the sphingosine-1-phosphate receptor family (S1PR) which play a crucial role in sphingolipid metabolism. Each of these receptors appears to be tissue specific and to have demonstrated roles in the regulation of cell proliferation and survival in various cancer types. Further analysis of the function that S1PRs serve in hematological malignancies offers a great potential for the discovery of novel and selective therapeutic agents targeting these receptors. This review focuses on the characterization of S1PRs and their roles in cancer development in various signaling pathways mediated through specific G coupled protein. In particular, pharmacological agents targeting these S1PRs will be discussed and their potential will be examined.